Systemic Review: Neurological Deficits following Ventriculoperitoneal Shunt (VPS) Insertion - Moshref, Rana; Algethmi, Rafaa Ahmed (Asian Journal of Neurosurgery, 2023)
A reduction in fluid absorption or an obstruction of normal outflow is a common cause of hydrocephalus. It typically requires medical attention, which frequently entails the placement of a ventriculoperitoneal shunt (VPS) to lower intracranial pressure. We intend to list the few, documented examples of neurological impairments resulting from the installation of a VPS in this systematic study. Two search engines (PubMed and Cochrane) were used to conduct a systematic review from 1975 to December 12, 2021. The following search terms were employed: neurological deficits or neurological injury or palsies or thalamus or tract or longitudinal fasciculus or somatotropy or fasciculus or hearing loss or hemisensory or cortico AND ventriculoperitoneal shunt or VPS AND hydrocephalus. The inclusion criteria included VPS, neurological deficits, and human participants. The exclusion criteria included ventriculoarterial shunt, lumboperitoneal shunt, nonhuman subjects, and infection. Twenty trials in total, including a total of 25 patients, were included. There were 17 case report studies. A total of 35/785 patients (4.46%) experienced neurological impairments. In 9/25 (36%) of shunt cases had one of the three recognized causes: trapped fourth ventricle, dandy walker, or syringomyelia. Most of the patients developed VI, VII nerve palsies 11/25 (44%) followed by weakness, cerebellar symptoms, and VI nerve palsy. The brainstem was seen to be the most often injured structure (15/25; 60%), followed by deep brain structures (thalamus, basal ganglia, and white matter tracts; 20%). Even though ventriculoperitoneal shunting is a routine and straightforward treatment, issues can still arise. Although rare, there have been reports of cranial nerve impairments, therefore care should be taken.
Keywords: neurological deficits; palsies; ventriculoperitoneal shunt; VPS; tract